DINAMIKA PENDIDIKAN ISLAM DI THAILAND PADA ABAD 19-20 - Aslan Aslan; Hifza Hifza; Muhammad Suhardi (Nazhruna: Jurnal Pendidikan Islam, 2020)
Thailand has two different parts of the region ranging from ethnics, culture, national and religion. However, due to religious differences, the trade route, which was a more profitable trading route in Southern Thailand, inhabited by Malay Patani, made the Siamese Kingdom want the area. The desires of the Siamese Kingdom were successful. So Patani Malay became part of the Thai Kingdom and its government system followed the policies adopted by the Thais, including in terms of Islamic education in Patani. Since then, conflicts began to occur as the policies adopted by the Thais were considered unsuitable for the Patani Malay in many various ways including forming an Islamic organization. As a result, the Patani could become independent without being under Thai auspices. However, these efforts and strategies have also not been successful, but only to negotiate so that conflicts can continue to be overcome both through cooperation with other Southeast Asia, the Middle East and Europe countries.